2017
DOI: 10.1093/nar/gkx540
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of in vitro evolution reveals the underlying distribution of catalytic activity among random sequences

Abstract: The emergence of catalytic RNA is believed to have been a key event during the origin of life. Understanding how catalytic activity is distributed across random sequences is fundamental to estimating the probability that catalytic sequences would emerge. Here, we analyze the in vitro evolution of triphosphorylating ribozymes and translate their fitnesses into absolute estimates of catalytic activity for hundreds of ribozyme families. The analysis efficiently identified highly active ribozymes and estimated cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…To identify the shortest ribozymes from our previously selected library of self-triphosphorylating ribozymes ( 30 ) with > 300 different ribozyme clusters ( 39 ), we followed a five-step procedure (figures 1 - 3). In the first step, 3′-truncated variants of the DNA pool were generated with the help of partially randomized primers and Klenow enzyme (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the shortest ribozymes from our previously selected library of self-triphosphorylating ribozymes ( 30 ) with > 300 different ribozyme clusters ( 39 ), we followed a five-step procedure (figures 1 - 3). In the first step, 3′-truncated variants of the DNA pool were generated with the help of partially randomized primers and Klenow enzyme (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Triphosphorylated RNA (5′-PPP) and RNA with a 5′-hydroxyl group (5′-OH) served as positive and negative control, respectively. The highly active ribozyme AP5 ( 39 ) was used as additional positive control. AP5 is 182 nucleotides in length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, non-enzymatic RNA polymerization (Prywes et al 2016;Zhang et al 2017;Hänle and Richert 2018), and the role of crowding (Saha et al 2018) and encapsulation (Bansho et al 2016;Matsumura et al 2016) are also becoming increasingly important factors for understanding plausible scenarios for chemical evolution and RNA replication at the origins of life. Furthermore, as high-throughput sequencing continues to fall in cost, RNA is re-emerging as an experimental model to explore evolutionary concepts such as the fitness landscape and epistasis (Pressman et al 2017(Pressman et al , 2019Bendixsen et al 2017).…”
Section: Prebiotic Evolution and The Rna World (Bottom Up)mentioning
confidence: 99%
“…Interestingly, in vitro experiments revealed the extreme versatility of random nucleic acids [35][36][37][38], and suggested that essential RNA molecules such as the hammerhead ribozyme could have multiple origins [39]. All together, these observations reinforce the plausibility of a spontaneous emergence of multiple functional sub-units.…”
mentioning
confidence: 95%